The evolution of inequality, heterogeneity and uncertainty in labor earnings in the US economy - Flavio Cunha; James Joseph Heckman (Institute for the Study of Labor (IZA), 2007)
A large empirical literature documents a rise in wage inequality in the American economy. It is silent on whether the increase in inequality is due to greater heterogeneity in the components of earnings that are predictable by agents or whether it is due to greater uncertainty faced by agents. Applying the methodology of Cunha, Heckman, and Navarro (2005) to data on agents making schooling decisions in different economic environments, we join choice data with earnings data to estimate the fraction of future earnings that is forecastable and how this fraction has changed over time. We find that both predictable and unpredictable components of earnings have increased in recent years. The increase in uncertainty is substantially greater for unskilled workers. For less skilled workers, roughly 60% of the increase in wage variability is due to uncertainty. For more skilled workers, only 8% of the increase in wage variability is due to uncertainty. Roughly 26% of the increase in the variance of returns to schooling is due to increased uncertainty. Using conventional measures of income inequality masks the contribution of rising uncertainty to the rise in the inequality of earnings for less educated groups.
Keywords: 330; Wage inequality; uncertainty; sorting; inequality accounting; Einkommensverteilung; Intertemporale Einkommensverteilung; Schulauswahl; Qualifikation; Risiko; USA